On Complete Convergence for Arrays of Rowwise Strong Mixing Random Variables (Communications in Mathematical Research, 2021)
In this paper, we present a general method to prove the complete convergence for arrays of rowwise strong mixing random variables, and give some results oncomplete convergence under some suitable conditions. Some Marcinkiewicz-Zygmundtype strong laws of large numbers are also obtained.
Keywords: complete convergence; rowwise dependence; strong mixing.